Thành phần hóa học và hoạt tính gây độc tế bào của loài kim giao núi đất (Nageia wallichiana) thu tại tỉnh Lâm Đồng. Phần 2. Các hợp chất biflavonoid, steroid và phenolic. - Liễu, Nguyễn Thị; Ninh, Phạm Thị; Phương Thảo, Trần Thị; Lộc, Trần Văn; Phòng, Đinh Thị; Hoàng Anh, Nguyễn Thị; Lưu, Nguyễn Thị; Chiến, Trần Văn; Sung, Trần Văn (Vietnam Journal of Chemistry, 2016)
In the frame work of the TÂY NGUYÊN 3 Program, the rare, ancient plant Nageia wallichiana (Kim giao núi đất) was collected in Lam Dong province and chemically, biologically studied. As results, three biflavonoids: amentoflavone (1), 4”’-O-methylamentoflavone (podocarpus flavone A) (2), 4’,4’’’,7’’-trimethoxyamentoflavone (3), 5a-hydroxystigmastane-6-one-3β-hexadecanoate (4), β-sitosterol (5) and 2-(4-hydroxyphenyl)-propane-1,3-diol (6) have been isolated. The structures of these compounds were determined by their MS, HR-MS, NMR, (1D and 2D) spectra and comparis on with the data in literatures. The cytotoxicity of compound 4 on eight human cancer cell lines has been tested. This is the first report of these compounds from Nageia wallichiana. Keywords. Nageia wallichiana, biflavonoids, amentoflavone, steroids, phenolic compound, cytotoxicity.